2012
DOI: 10.1007/s00540-012-1529-9
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of aprepitant to prevent postoperative nausea in highly susceptible patients after gynecological laparoscopy

Abstract: Aprepitant 80 mg orally was effective in lowering the incidence of PONV in the first 48 h after anesthesia in patients receiving fentanyl-based PCA after gynecological laparoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 21 publications
2
41
0
3
Order By: Relevance
“…Two trials reported isolated QT prolongation in a few patients, but with no clinical significance. Seon Jung et al 15 reported abdominal distension with aprepitant and dose-dependent dizziness in the 125 mg group. Multiple trials reported that aprepitant led to a fall in the incidence of vomiting, although nausea scores at various time points were not statistically different, highlighting a unique but not fully understood mechanism of action for aprepitant.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Two trials reported isolated QT prolongation in a few patients, but with no clinical significance. Seon Jung et al 15 reported abdominal distension with aprepitant and dose-dependent dizziness in the 125 mg group. Multiple trials reported that aprepitant led to a fall in the incidence of vomiting, although nausea scores at various time points were not statistically different, highlighting a unique but not fully understood mechanism of action for aprepitant.…”
Section: Resultsmentioning
confidence: 98%
“…However, although most chemotherapy-related antiemetic regimes used 125 mg oral aprepitant,20 there are no dose recommendations for the perioperative use of aprepitant. Most PONV-related trials have used oral doses ranging from 40 to 125 mg without major adverse effects, except for one study which reported dizziness with 125 mg in comparison with 80 mg 15. For any new drug, the dose recommendations will depend upon the antiemetic efficacy and the side effect profile.…”
Section: Discussionmentioning
confidence: 99%
“…NK1-RAs are nonsedating and do not cause QTc prolongation, although aprepitant does inhibit CYP3A4 in a dose-dependent fashion. 3,38,45,49-51 A recent trial reported no difference in PDNV from 24 to 48 hours postoperatively in patients receiving aprepitant versus placebo 52 ; although it could be an important adjunct in the prevention of PDNV, further investigation into aprepitant's impact in the postdischarge period is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed a wide range of prevention effects of antiemetic drugs (22.9 − 77.8%), depending on which drugs were administered for PONV prevention in patients indicated for laparoscopic surgery [11]. Park et al [12] reported a 66% treatment completion rate when palonosetron was administered for PONV prevention in patients indicated for gynaecologic laparoscopic surgery, and Jung et al [13] reported 56% and 63% treatment completion rates in the 80- and 125-mg aprepitant groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl is an opioid and represents the major cause of PONV. Unlike in the studies by Park et al [12] and Jung et al [13], in this study, the basal infusion dose of fentanyl was not set via IV-PCA. Therefore, its dose was reduced when our patients experienced less pain, which might also explain the high PONV treatment completion rate in this study.…”
Section: Discussionmentioning
confidence: 99%